Термогазодинаміка одиночної циліндричної поверхні з заглибленнями на зовнішній стороні - Халатов, А. А.; Мейріс, А. Ж.; Гамрецька, А. В. (Енергетика і автоматика, 2017)
Thermogasdynamics cylindrical surface with a recess on the outer sideА. Khalatov, A. Meyris, A. Gamretskaya Reducing the weight and dimensions of heat exchangers heating is an urgent problem. The most promising way to solve this problem - the intensification of heat transfer.Now for external heat intensifying widely used different methods of profiling pipes and causing an artificial roughness. Such methods include intensifying method using near-wall intensifiers such as applying spherical indentations on the surface of the cylinder is one of the most effective. Using this method causes the shift of separation in the rear area of the pipe, which positively affects the heat transfer. There follows an intensification has a significant advantage and high energy efficiency by only a wall turbulence flow field.In the current turbulent motion to recess smerchepodibnyh observed the formation of vortex structures demolished course with some frequency. The system leads to depressions nonlinear interaction of individual vortices. Specific vortex structure, three-dimensional and unsteady zavyhrenist had vortices above the height of the indentations provide high heat and relatively low pressure loss.The purpose of research - to establish the physics of heat exchange intensification transverse flow around cylindrical surfaces with spherical indentations on the outside by means of numerical simulation.Materials and methods of research. Numerical simulation of heat transfer processes of cylindrical surfaces with grooves on the outer surface held in a commercial package ANSYS CFX.Calculations were made for Reynolds numbers 8000, 10000, 15000.Boundary conditions was set as follows: flow rate constant with temperature 22 degrees respectively at the input and the output pressure, the study asked a surface boundary conditions of the first kind t = 0 ° C, the horizontal sides of the channel wondered symmetric boundary conditions, and on the other - periodic boundary conditions.For the mathematical simulation model was chosen SST turbulence as the model that is most often used to calculate the heat exchange of similar objects.Results. As a result of numerical modeling of heat transfer processes in the flow around a cylinder with grooves using the software package ANSYS CFX turbulence model using SST TT received physical structure of the picture stream.From the analysis of the figures velocity vector fields suggests that the reason is intensifying turbulence indentations boundary layer. There is a local destruction (separation) boundary layer in the cavity, resulting in reduced thermal resistance. Also a positive effect on local heat transfer vyhroutvorennya.Using numerical modeling scripting intensity distribution of heat in a circle. It was established that the main causes of heat is intensifying turbulence flow for the deepening and the initial edge recess.Comparing the distribution of heat transfer coefficients for smooth cylinder and cylinder with grooves for leads to the conclusion that the investigated surface heat transfer coefficient greater than the heat transfer coefficient similar smooth surface.As a result of numerical modeling of heat processes of cylindrical surfaces with grooves on the outer surface, found that the application of depressions caused an increase in average heat transfer by 7.4% and hydraulic resistance by 11%. Thus, Reynolds analogy factor is 0.97.ConclusionsMathematical modeling termohazodynamiky tsylidnrychnoyi surface of the outer grooves on the side. It was determined that the cause is intensyfikatsiyi turbulizatsiya boundary layer on grooves and the original edge of the recess. Also a positive effect on local heat transfer vyhroutvorennya.It's revealed that the application of grooves on cylindrical surface almost does not affect the separation zone in the test speed range for single cylinder.Application of grooves on the surface zbilshylo teploviddachi intensity by 7.4% and hydraulic resistance by 11%. Reynolds analogy factor is 0.97.